Active Tourism and Intermodality: Railway Stations as Soft Mobility Hubs—An Assessment Framework for Italy - Giulio Senes; Paolo Stefano Ferrario; Federico Riva; Natalia Fumagalli; Denise Corsini; Anna Donati; Luigi Contestabile; Stefano Fondi; Roberto Rovelli (Land)
Since tourism involves the movement of people, mobility and tourism are deeply interconnected, with mutual growth dynamics but also shared negative effects, such as greenhouse gas emissions. Among the wide spectrum of policies and strategies for making tourism sustainable, soft mobility has gained increasing importance, becoming more and more a widespread form of active tourism, especially after the COVID-19 pandemic. A sustainable approach, aimed at maintaining a balance between economic development and environmental protection, requires greater promotion of soft mobility and integration with rail transport. To make active tourism truly sustainable, the support of the railway network, a low-emission collective transport system, is needed, allowing people to reach destinations and move between destinations, taking advantage of intermodality. This needs the improvement of the connection between the two transport systems, the creation of services for visitors, and the organization of an appropriate railway service. Within this framework, the present work defines a methodology that, starting from the analysis of the relationships between railway stations, the soft mobility network, and attractions in the surrounding territory, allows us to identify stations that could serve as intermodal hubs for connecting local resources through soft mobility, according to a priority scale defined by the Soft Mobility HUB (SMH) Index. The methodology, applied to Italian railway stations, is based on the use of GIS (Geographic Information System) and AHP (Analytic Hierarchy Process), allowing a rigorous, transparent, and participatory approach. The proposed model, which is replicable in other contexts, has been effective in identifying, in different scenarios, the stations most suitable for becoming hubs for soft mobility. It can serve as a support tool for decision-makers to maximize investments by focusing on stations capable to provide the greatest contribution to the development of active and diversified tourism.